High performance composite material for phase shifter and method of making the same

By preparing recycled iron oxide and compounding it with other components, the problems of high dielectric loss and large ferromagnetic resonance linewidth of existing ferrite phase shifter materials are solved, the preparation of high-performance composite materials and the recycling of iron oxide waste are realized, and the stability and efficiency of the material are improved.

CN120463490BActive Publication Date: 2025-10-17SEVEN STAR COMM TECH (BEIJING) CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510555599.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-04-29
Publication Date
2025-10-17
Estimated Expiration
2045-04-29

AI Technical Summary

Technical Problem

Existing ferrite phase shifter materials have high dielectric loss and large ferromagnetic resonance linewidth, making it impossible to recycle iron oxide waste.

Method used

Regenerated iron oxide is prepared by high-temperature roasting and alkaline solution treatment of iron oxide waste, and then compounded with lithium carbonate, lanthanum-doped zinc oxide quantum dots, rutile and anatase titanium dioxide, manganese tetraoxide, bismuth trioxide and additives to prepare high-performance composite materials. Cerium-doped and lanthanum-doped zinc oxide quantum dots are used to fill lattice defects and reduce dielectric loss and ferromagnetic resonance linewidth.

Benefits of technology

It effectively reduces dielectric loss and ferromagnetic resonance linewidth, realizes the recycling of iron oxide waste, and improves the performance stability and efficiency of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application belongs to the technical field of electronic ceramic materials, and particularly relates to a high-performance composite material for a phase shifter and a preparation method thereof. The high-performance composite material for the phase shifter is prepared by using regenerated iron oxide obtained by sequentially performing high-temperature roasting and alkali treatment on iron oxide waste, doping treatment of the regenerated iron oxide with cerium oxide, and then mixing the regenerated iron oxide with lithium carbonate, zinc oxide, titanium dioxide, trimanganese tetroxide, bismuth trioxide and an additive, so that the dielectric loss is effectively reduced, and the ferromagnetic resonance line width is narrowed.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of electronic ceramic materials, and particularly relates to a high-performance composite material for a phase shifter and a preparation method thereof. BACKGROUND

[0002] The ferrite material for a phase shifter is a key material in the fields of microwave communication, radar, satellite communication and the like, and the performance of the ferrite material directly affects the phase adjustment capability, power capacity, stability and efficiency of the phase shifter. Compared with other phase shifters, the ferrite phase shifter has smaller insertion loss, better stability and larger power capacity, and the phase shifting degree can also be made very large. The ferrite material is a composite oxide material composed of iron oxide and other metal oxides. In terms of electrical properties, the resistivity of the ferrite material is much larger than that of metal and alloy magnetic materials, and the ferrite material also has higher dielectric properties. The magnetic properties of the ferrite material are manifested as high magnetic permeability at high frequencies.

[0003] A Chinese patent (publication number CN103880408B) discloses a high-performance high-densification lithium ferrite material for a phase shifter and a preparation method thereof. The material is composed of a main component and an additive. The main component is composed of Fe2O3, Li2CO3, TiO2, ZnO, MnCO3 and Bi2O3, and the weight fractions of the components are 65-75 parts, 9-12 parts, 8-14 parts, 3-4 parts, 1-6 parts and 0.1-1 part, respectively. The additive is 0.2-3wt% of the main component. After ball milling and drying, the components are calcined, and then ball milled again. The milled components are granulated by a spray granulator. The obtained dry powder is pressed into a blank by a dry powder press, and then pressed into a blank by an isostatic press. Finally, the blank is sintered in a furnace. However, the dielectric loss of the material prepared by the patent technology needs to be optimized, the ferromagnetic resonance line width is relatively large, and the waste material cannot be recycled, which affects the further use of the material.

[0004] Therefore, there is an urgent need for a high-performance composite material for a phase shifter, which can regenerate and utilize iron oxide waste, screen specific raw material components, effectively reduce dielectric loss, and narrow the ferromagnetic resonance line width. SUMMARY

[0005] The application aims to provide a high-performance composite material for a phase shifter and a preparation method thereof. The application regenerates iron oxide waste by sequentially performing high-temperature roasting and alkali treatment, and then doping with cerium oxide to obtain regenerated iron oxide. Then, the regenerated iron oxide is prepared together with lithium carbonate, zinc oxide, titanium dioxide, trimanganese tetroxide, bismuth trioxide and an additive to obtain a high-performance composite material for a phase shifter, which effectively reduces dielectric loss and narrows the ferromagnetic resonance line width.

[0006] In order to achieve the above-mentioned purpose, the application provides the following technical solutions:

[0007] A first aspect of the present invention provides a high performance composite material for a phase shifter.

[0008] The invention comprises the following components in parts by weight: 60-70 parts of regenerated iron oxide, 10-14 parts of lithium carbonate, 18-22 parts of zinc oxide, 8-12 parts of titanium dioxide, 2-4 parts of manganese tetraoxide, 0.2-0.4 parts of bismuth trioxide and 1-3 parts of additives.

[0009] As a preferred solution, the weight parts of the regenerated iron oxide in the present invention can be 60 parts, 62 parts, 64 parts, 66 parts, 68 parts or 70 parts, etc.

[0010] As a preferred solution, the weight parts of the lithium carbonate in the present invention can be 10 parts, 11 parts, 12 parts, 13 parts or 14 parts.

[0011] As a preferred solution, the weight proportion of the zinc oxide in the present invention can be 18 parts, 19 parts, 20 parts, 21 parts or 22 parts.

[0012] As a preferred solution, the weight proportion of the titanium dioxide in the present invention can be 8 parts, 9 parts, 10 parts, 11 parts or 12 parts.

[0013] As a preferred solution, the weight proportion of the trimanganese tetraoxide in the present invention can be 2 parts, 2.5 parts, 3 parts, 3.5 parts or 4 parts.

[0014] As a preferred solution, the weight proportion of the bismuth trioxide in the present invention can be 0.2 parts, 0.25 parts, 0.3 parts, 0.35 parts or 0.4 parts, etc.

[0015] As a preferred solution, the weight proportion of the additive in the present invention can be 1 part, 1.5 parts, 2 parts, 2.5 parts or 3 parts.

[0016] As a preferred solution, the preparation method of the regenerated iron oxide includes: first high-temperature roasting the iron oxide waste, and then treating it with alkaline solution to obtain impurity-removed iron oxide; using cerium trioxide to dope the impurity-removed iron oxide to obtain regenerated iron oxide.

[0017] As a preferred scheme, the preparation method of the regenerated iron oxide comprises: taking 60-70 parts of iron oxide waste for high-temperature roasting (temperature is 780-800 DEG C, time is 100-120 min), after cooling, adding to 120-140 parts of sodium hydroxide solution with a concentration of 40-50 g / L, stirring at 34-38 DEG C for 50-60 min, filtering, drying, and obtaining impurity-removed iron oxide; taking 60-70 parts of the impurity-removed iron oxide, adding to a sulfuric acid solution with a mass concentration of 6-8%, then adding 1-3 parts of cerium sesquioxide, stirring at 80-90 DEG C for 100-120 min, aging for 3-5 h, suction filtering, drying the filter cake, sintering at 800-820 DEG C for 80-90 min, cooling, and grinding to obtain regenerated iron oxide.

[0018] The present application can effectively remove impurity elements in the iron oxide waste and improve the purity of the iron oxide by sequentially performing high-temperature roasting and alkali treatment on the iron oxide waste; then the regenerated iron oxide is obtained by doping treatment with cerium sesquioxide. The doping of cerium in the regenerated iron oxide can change the relaxation process of the interface polarization and the dipole polarization in the composite material, reduce the energy loss caused by polarization hysteresis, inhibit the lattice defects of the iron oxide, weaken the defect-induced dielectric relaxation loss, and thus reduce the conduction loss; the cerium doping can fill the lattice defects, reduce the non-magnetic impurities or local magnetic disordered regions, reduce the unevenness of the magnetic anisotropy distribution, fix the position of the magnetic domain wall, reduce the magnetic relaxation loss caused by the domain wall movement, and narrow the ferromagnetic resonance line width.

[0019] As a preferred scheme, the zinc oxide is lanthanum-doped zinc oxide quantum dots.

[0020] The lanthanum-doped zinc oxide quantum dots can fill the oxygen vacancies by lanthanum doping, reduce the concentration of free electrons, and thus reduce the conduction loss; meanwhile, the lanthanum element and the zinc oxide quantum dots jointly reduce the concentration of oxygen vacancies and other shallow level defects, thereby inhibiting the relaxation loss caused by the interface polarization and the space charge polarization, and reducing the dielectric loss of the material; after the lanthanum doping fills the oxygen vacancies of the zinc oxide quantum dots, the defects at the grain boundaries are reduced, the resistance of the magnetic domain wall movement is reduced, the magnetic hysteresis loss is reduced, the lattice strain is generated by the quantum confinement effect of the zinc oxide quantum dots, the ferromagnetic anisotropy field of the ferrite is homogenized through interface transmission, and the ferromagnetic resonance line width of the composite material is narrowed.

[0021] As a preferred scheme, the titanium dioxide is rutile titanium dioxide and anatase titanium dioxide.

[0022] As a preferred scheme, the mass ratio of the rutile titanium dioxide and the anatase titanium dioxide is (1-2):1.

[0023] As a preferred scheme, the particle size of the rutile titanium dioxide is 20-200 nm; and the particle size of the anatase titanium dioxide is 50-300 nm.

[0024] The present application is characterized in that the dense crystal lattice of the rutile titanium dioxide can fill the defects of the anatase, reduce the free carrier concentration, and thus reduce the conductive loss; the surface oxygen vacancies of the anatase titanium dioxide can capture free electrons, reduce the carrier mobility, and the defect dipoles at the interface of the rutile-anatase two phases can delay the polarization relaxation; in addition, the dense crystal lattice of the rutile titanium dioxide can reduce the resistance of the magnetic domain wall movement, and the lattice distortion of the anatase can be coupled with the magnetic moment of the ferrite to inhibit the magnetic domain wall jitter, and the synergistic effect can reduce the ferromagnetic resonance line width.

[0025] As a preferred scheme, the additive is selected from vanadium pentoxide or nickel oxide.

[0026] The second aspect of the present application provides a preparation method of the high-performance composite material for the phase shifter according to the first aspect, comprising the following steps:

[0027] S1: 60-70 parts of the regenerated iron oxide, 10-14 parts of lithium carbonate, 18-22 parts of zinc oxide, 8-12 parts of titanium dioxide, 2-4 parts of trimanganese tetroxide, 0.2-0.4 parts of bismuth trioxide, and 1-3 parts of the additive are mixed and ball milled in weight parts, dried to obtain a grinding material;

[0028] S2: the grinding material is sieved, granulated, and press-formed, and then transferred to a sintering furnace for sintering treatment, and cooled to room temperature to obtain the high-performance composite material for the phase shifter.

[0029] As a preferred scheme, the ball milling time is 6-8 h.

[0030] As a preferred scheme, the sintering treatment temperature is 880-900 DEG C, and the time is 100-120 min.

[0031] Compared with the prior art, the present application has the following advantages and beneficial effects:

[0032] 1. The cerium doping in the regenerated iron oxide can change the relaxation process of the interface polarization and the dipole polarization in the composite material, reduce the energy loss caused by the polarization hysteresis, inhibit the lattice defects of the iron oxide, weaken the defect-induced dielectric relaxation loss, and thus reduce the conductive loss; the cerium doping can fill the lattice defects, reduce the non-magnetic impurities or local magnetic disordered areas, reduce the unevenness of the magnetic anisotropy distribution, fix the position of the magnetic domain wall, reduce the magnetic relaxation loss caused by the domain wall movement, and narrow the ferromagnetic resonance line width.

[0033] 2、The lanthanum-doped zinc oxide quantum dots of the present application can fill oxygen vacancies through lanthanum doping, reduce the concentration of free electrons, thereby reducing the conduction loss, and the lanthanum element and the zinc oxide quantum dots jointly reduce the concentration of oxygen vacancy and other shallow level defects, thereby inhibiting the relaxation loss caused by the interface polarization and the space charge polarization, and reducing the dielectric loss of the material; after the lanthanum-doped filling of the oxygen vacancies of the zinc oxide quantum dots, the defects at the grain boundaries are reduced, the magnetic domain wall movement resistance is reduced, the hysteresis loss is reduced, the lattice strain generated by the zinc oxide quantum dots is matched, the interface transmission makes the magnetic crystal anisotropy field of the ferrite uniform, and the ferromagnetic resonance line width of the composite material is narrowed.

[0034] 3、The present application can reduce the free carrier concentration by matching the rutile titanium dioxide and the anatase titanium dioxide and controlling the particle size of the two, the dense lattice of the rutile titanium dioxide can fill the defects of the anatase, thereby reducing the conduction loss, the surface oxygen vacancies of the anatase titanium dioxide can capture free electrons, thereby reducing the carrier mobility, and the defect dipoles at the interface of the rutile-anatase two phases can delay the polarization relaxation; in addition, the dense lattice of the rutile titanium dioxide can reduce the magnetic domain wall movement resistance and the hysteresis loss, and the lattice distortion of the anatase can be coupled with the magnetic moment of the ferrite to inhibit the magnetic domain wall jitter, and the two work together to reduce the ferromagnetic resonance line width. DETAILED DESCRIPTION

[0035] The technical solutions in the embodiments of the present application will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative labor fall within the scope of protection of the present application.

[0036] Some components in the examples and comparative examples are as follows:

[0037] Iron oxide waste, commercially available;

[0038] Cerium sesquioxide, CAS No. 1345-13-7, purchased from Shanghai Huayuan Century Trading Co., Ltd.;

[0039] Lithium carbonate, CAS No. 554-13-2, purchased from China Reagent Co., Ltd.;

[0040] Commercially available zinc oxide, product number Z431819, purchased from Shanghai Aldrin Biochemical Technology Co., Ltd.;

[0041] Lanthanum-doped zinc oxide quantum dots, product number Q-0313737, purchased from Xi'an Qiyue Biological Technology Co., Ltd.;

[0042] Rutile titanium dioxide I, product number T104942, particle size 25 nm, purchased from Shanghai Aladdin Biochem Technology Co., Ltd.;

[0043] Rutile titanium dioxide II, product number XFI73, particle size 600 nm, purchased from Jiangsu Xianfeng Nanometer Material Technology Co., Ltd.;

[0044] Anatase titanium dioxide I, product number T104946, particle size 100 nm, purchased from Shanghai Aladdin Biochem Technology Co., Ltd.;

[0045] Anatase titanium dioxide II, product number XFI81, particle size 800 nm, purchased from Jiangsu Xianfeng Nanometer Material Technology Co., Ltd.;

[0046] Trimanganese tetroxide, CAS number 1317-35-7, purchased from Shanghai Macklin Biochemical Technology Co., Ltd.;

[0047] Bismuth trioxide, CAS number 1304-76-3, purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0048] Vanadium pentoxide, CAS number 1314-62-1, purchased from Shanghai Macklin Biochemical Technology Co., Ltd.;

[0049] Nickel oxide, CAS number 1313-99-1, purchased from Shanghai Macklin Biochemical Technology Co., Ltd.;

[0050] Example 1

[0051] The embodiment provides a preparation method of a high-performance composite material for a phase shifter, and the method comprises the following steps:

[0052] S1: 70 parts of regenerated iron oxide, 14 parts of lithium carbonate, 22 parts of lanthanum-doped zinc oxide quantum dots, 12 parts of titanium dioxide (8 parts of rutile titanium dioxide I and 4 parts of anatase titanium dioxide I), 4 parts of trimanganese tetroxide, 0.4 parts of bismuth trioxide and 3 parts of additive vanadium pentoxide are mixed and ball milled for 8 h in weight parts, dried, and ground material is obtained;

[0053] S2: The ground material is sieved, granulated, and compression molded, and then transferred to a sintering furnace for sintering treatment (temperature is 900 DEG C, and time is 100 min), and cooled to room temperature to obtain the high-performance composite material for the phase shifter.

[0054] The preparation of the regenerated iron oxide: 70 parts of iron oxide waste is high-temperature calcined (temperature is 800 DEG C, time is 100 min), and after cooling, it is added to 140 parts of a sodium hydroxide solution with a concentration of 40 g / L, stirred at 38 DEG C for 50 min, filtered, dried, and obtained as impurity-removed iron oxide; 70 parts of the impurity-removed iron oxide is added to a sulfuric acid solution with a mass concentration of 8%, and then 3 parts of cerium sesquioxide is added, stirred at 90 DEG C for 100 min, aged for 5 h, suction filtered, the filter cake is dried, sintered at 820 DEG C for 80 min, cooled, and ground to obtain regenerated iron oxide.

[0055] Example 2

[0056] The embodiment provides a preparation method of a high-performance composite material for a phase shifter, including the following steps:

[0057] S1: 60 parts of regenerated iron oxide, 10 parts of lithium carbonate, 18 parts of lanthanum-doped zinc oxide quantum dots, 8 parts of titanium dioxide (4 parts of rutile titanium dioxide I and 4 parts of anatase titanium dioxide I), 2 parts of trimanganese tetroxide, 0.2 parts of bismuth trioxide, and 1 part of an additive nickel oxide are mixed and ball milled for 6 h, dried, and obtained as a grinding material;

[0058] S2: the grinding material is sieved, granulated, and press-formed, and then transferred to a sintering furnace for sintering treatment (temperature is 880 DEG C, time is 120 min), and cooled to room temperature to obtain a high-performance composite material for a phase shifter.

[0059] The preparation of the regenerated iron oxide: 60 parts of iron oxide waste is high-temperature calcined (temperature is 780 DEG C, time is 120 min), and after cooling, it is added to 120 parts of a sodium hydroxide solution with a concentration of 50 g / L, stirred at 34 DEG C for 60 min, filtered, dried, and obtained as impurity-removed iron oxide; 60 parts of the impurity-removed iron oxide is added to a sulfuric acid solution with a mass concentration of 8%, and then 1 part of cerium sesquioxide is added, stirred at 80 DEG C for 120 min, aged for 3 h, suction filtered, the filter cake is dried, sintered at 820 DEG C for 80 min, cooled, and ground to obtain regenerated iron oxide.

[0060] Example 3

[0061] The embodiment provides a preparation method of a high-performance composite material for a phase shifter, including the following steps:

[0062] S1: 65 parts of regenerated iron oxide, 12 parts of lithium carbonate, 20 parts of lanthanum-doped zinc oxide quantum dots, 10 parts of titanium dioxide (6 parts of rutile titanium dioxide I and 4 parts of anatase titanium dioxide I), 3 parts of trimanganese tetroxide, 0.3 parts of bismuth trioxide, and 2 parts of additive nickel oxide are mixed and ball-milled for 7 h in parts by weight, dried, to obtain a grinding material;

[0063] S2: The grinding material is sieved, granulated, press-formed, and then transferred to a sintering furnace for sintering treatment (temperature of 890°C, time of 110 min), and cooled to room temperature to obtain a high-performance composite material for a phase shifter.

[0064] Preparation of the regenerated iron oxide: 65 parts of iron oxide waste is high-temperature calcined (temperature of 790°C, time of 110 min), and after cooling, is added to 130 parts of a sodium hydroxide solution with a concentration of 45 g / L, stirred at 35°C for 55 min, filtered, dried, to obtain impurity-removed iron oxide; 65 parts of the impurity-removed iron oxide is added to a sulfuric acid solution with a mass concentration fraction of 7%, and then 2 parts of cerium trioxide is added, stirred at 85°C for 110 min, and aged for 4 h, suction-filtered, the filter cake is dried, sintered at 810°C for 85 min, cooled, and ground, to obtain regenerated iron oxide.

[0065] Comparative Example 1

[0066] The difference between this comparative example and Example 1 is that impurity-removed iron oxide is used instead of regenerated iron oxide.

[0067] Comparative Example 2

[0068] The difference between this comparative example and Example 1 is that iron oxide waste is used instead of regenerated iron oxide.

[0069] Comparative Example 3

[0070] The difference between this comparative example and Example 1 is that commercially available zinc oxide (item number Z431819) is used instead of lanthanum-doped zinc oxide quantum dots.

[0071] Comparative Example 4

[0072] The difference between this comparative example and Example 1 is that rutile titanium dioxide II (item number XFI73, particle size of 600 nm) is used instead of rutile titanium dioxide I (item number T104942, particle size of 25 nm).

[0073] Comparative Example 5

[0074] The difference between this comparative example and Example 1 is that anatase titanium dioxide II (item number XFI81, particle size of 800 nm) is used instead of anatase titanium dioxide I (item number T104946, particle size of 100 nm).

[0075] Comparative Example 6

[0076] The difference between this comparative example and Example 1 is that the amount of rutile titanium dioxide I is changed to 10 parts, and the amount of anatase titanium dioxide I is changed to 2 parts.

[0077] Comparative Example 7

[0078] The difference between this comparative example and Example 1 is that the amount of rutile titanium dioxide I is changed to 4 parts, and the amount of anatase titanium dioxide I is changed to 8 parts.

[0079] Performance Testing

[0080] The performance test of the composite material was carried out with reference to the requirements of GB / T 9633-2012 Method for measuring the properties of gyromagnetic materials for microwave frequency applications.

[0081] Table 1 Performance test results

[0082]

[0083] It can be seen from the above performance test results that Examples 1-3 have the best comprehensive performance. This is mainly because the waste iron oxide is subjected to high-temperature calcination and alkaline solution treatment in sequence, and then doped with cerium trioxide to obtain regenerated iron oxide, which is then prepared together with lithium carbonate, lanthanum-doped zinc oxide quantum dots, titanium dioxide (a compound of rutile titanium dioxide and anatase titanium dioxide), manganese tetraoxide, bismuth trioxide and additives to obtain a high-performance composite material for phase shifters, which effectively reduces dielectric loss and narrows the ferromagnetic resonance linewidth.

[0084] Compared with Example 1, the dielectric loss of Comparative Example 1 is increased and the ferromagnetic resonance line width is enlarged because the impure iron oxide is used instead of the regenerated iron oxide and the cerium doping is absent. Compared with Example 1, the dielectric loss of Comparative Example 2 is increased and the ferromagnetic resonance line width is enlarged because the waste iron oxide is used instead of the regenerated iron oxide and the cerium doping is absent. Compared with Example 1, the dielectric loss of Comparative Example 3 is increased and the ferromagnetic resonance line width is enlarged because the commercially available zinc oxide (product number Z431819) is used instead of the lanthanum-doped zinc oxide quantum dots and the lanthanum element and the quantum dots are absent. Compared with Example 1, the dielectric loss of Comparative Example 4 is increased and the ferromagnetic resonance line width is enlarged because the rutile titanium dioxide II (product number XFI73, particle size 600 nm) is used instead of the rutile titanium dioxide I (product number T104942, particle size 25 nm) and the rutile titanium dioxide II has a large particle size and a poor compounding effect. Compared with Example 1, the dielectric loss of Comparative Example 5 is increased and the ferromagnetic resonance line width is enlarged because the anatase titanium dioxide II (product number XFI81, particle size 800 nm) is used instead of the anatase titanium dioxide I (product number T104946, particle size 100 nm) and the anatase titanium dioxide II has a large particle size and a poor compounding effect. Compared with Example 1, the dielectric loss of Comparative Example 6 is increased and the ferromagnetic resonance line width is enlarged because the amount of the rutile titanium dioxide I is changed to 10 parts and the amount of the anatase titanium dioxide I is changed to 2 parts and the rutile titanium dioxide I has a large amount and a poor compounding effect. Compared with Example 1, the dielectric loss of Comparative Example 7 is increased and the ferromagnetic resonance line width is enlarged because the amount of the rutile titanium dioxide I is changed to 4 parts and the amount of the anatase titanium dioxide I is changed to 8 parts and the anatase titanium dioxide I has a large amount and a poor compounding effect.

Claims

1. A high-performance composite material for a phase shifter, characterized in that: The composition comprises the following components in parts by weight: 60-70 parts of regenerated iron oxide, 10-14 parts of lithium carbonate, 18-22 parts of zinc oxide, 8-12 parts of titanium dioxide, 2-4 parts of manganese tetraoxide, 0.2-0.4 parts of bismuth trioxide and 1-3 parts of additives; The preparation method of the regenerated iron oxide comprises: firstly subjecting the iron oxide waste to high temperature roasting, and then subjecting it to alkaline solution treatment to obtain impurity-removed iron oxide; and then subjecting the impurity-removed iron oxide to doping treatment with cerium trioxide to obtain regenerated iron oxide. The high temperature calcination conditions include: temperature of 780-800°C and time of 100-120 minutes; The alkali solution treatment step comprises: adding 60-70 parts by weight of the iron oxide waste to 120-140 parts of a sodium hydroxide solution having a concentration of 40-50 g / L, stirring at 34-38° C. for 50-60 minutes, filtering, and drying; The doping treatment step includes: adding 60-70 parts of impurity-removed iron oxide to a sulfuric acid solution with a mass concentration of 6-8% by weight, then adding 1-3 parts of cerium trioxide, stirring at 80-90° C. for 100-120 minutes, aging for 3-5 hours, filtering, drying the filter cake, sintering at 800-820° C. for 80-90 minutes, cooling, and grinding.

2. The high-performance composite material for phase shifter according to claim 1, characterized in that: The zinc oxide is lanthanum-doped zinc oxide quantum dots.

3. The high-performance composite material for phase shifter according to claim 1, characterized in that: The titanium dioxide is rutile titanium dioxide and anatase titanium dioxide.

4. The high-performance composite material for a phase shifter according to claim 3, characterized in that: The mass ratio of the rutile titanium dioxide to the anatase titanium dioxide is (1-2):

1.

5. The high performance composite material for phase shifter according to claim 4, characterized in that: The particle size of the rutile titanium dioxide is 20-200 nm; the particle size of the anatase titanium dioxide is 50-300 nm.

6. The high-performance composite material for phase shifter according to claim 1, characterized in that: The additive is selected from vanadium pentoxide or nickel oxide.

7. A method for preparing a high-performance composite material for a phase shifter according to claim 1, characterized in that: The following steps are involved: S1: In parts by weight, 60-70 parts of regenerated iron oxide, 10-14 parts of lithium carbonate, 18-22 parts of zinc oxide, 8-12 parts of titanium dioxide, 2-4 parts of manganese tetraoxide, 0.2-0.4 parts of bismuth trioxide and 1-3 parts of additives are mixed and ball-milled, and dried to obtain an abrasive; S2: The abrasive is sieved, granulated, pressed and formed, and then transferred to a sintering furnace for sintering treatment, and cooled to room temperature to obtain a high-performance composite material for a phase shifter.

Citation Information

Patent Citations

  • High-performance high-compaction lithium ferrite material for phase shifter, and preparation method thereof

    CN103880408B

  • Low-temperature-sintered low-loss LiZn ferrite material and preparation method

    CN109053180A

  • Low-loss microwave ferrite material for LTCF phase shifter and preparation method of low-loss microwave ferrite material

    CN118373677A